Development of Underground Water Treatment System at Pusat Bimbingan Insan Kg Kabog, Kunak, Sabah - Wan Faizal, Wan Ishak; Mohammad Adam, Azman; Muhamad Aliff, Ramli (Knowledge Transfer Centre, USM, 2016)
Malaysia is a country with rich water resources including its surface water such as river, reservoir, lake, sea and ground water. In general, Malaysia has an abundance of water either on surface or underground. However, the supply of clean water is decreasing while demand is growing parallel to the population increment. Hence, an alternative has been chosen and implemented to assist the people of Pusat Bimbingan Insan Kg Kabog, Kunak, Sabah to deal with this demand. This project was divided into two stages, the preliminary stage where the system is designed based on the early parameter and the construction stage where the system is built and the equalization tank, sedimentation, open bed media and filtration system are installed. The water samples are taken from both influence and effluence to be analysed. The samples are analysed using ICPMS for Potassium (K), Sodium (Na), Calcium (Ca), Magnesium (Mg), Iron (Fe), Manganese (Mn), Sulphate (SO4), Bicarbonate (CO3) and Chloride (Cl). The result showed that all the water parameter tested is in accordance with the drinking water standards and safe to be consumed. In additionally it also removes the odour and taste of underground water which often exists. Therefore, the use of underground water in daily life can be an alternative to replace the current source of water used in Malaysia, whereby the area required for this system is adequate to be installed in schools, agricultural and industrial sectors in Malaysia.